Programa de organizadores gráficos para mejorar la comprensión lectora de textos en estudiantes del quinto grado de una Institución Educativa-Alto Trujillo, 2018 - Ramirez Valdivieso, Katerin Steffani (2019)
The objective of the present work was to determine the influence of the Graphic Organizers program to improve reading comprehension in the fifth grade Primary Education students of the educational institution Nª. 82105 Solaris Concerted School, for which a sample of 55 students is used (28 from the control group and 27 students for the experimental group) a 20-item test is applied to them. Then, from the application of the Program, the experimental group shows an improvement in reading comprehension, such as the evidence of the calculated T value (3,073) with a significance level of 1,706.